Preoperative atrial fibrillation in association with reduced haemoglobin predicts increased 30-d mortality after cardiac surgery. (5th April 2021) - Räsänen, Jenni; Juutilainen, Auni; Halonen, Jari
Abstract: Objectives: Atrial fibrillation is the most common arrhythmia occurring after cardiac surgery. Less attention has been focused on preoperative atrial fibrillation and anaemia as risk factors for mortality after cardiac surgery. The aim of this study was to determine preoperative risk factors for 30-d mortality after open-heart surgery. Design . The study population consisted of 2015 patients (73.4% men; mean age 68 years) undergoing coronary artery bypass grafting (CABG) (52.0%), aortic valve replacement (AVR) (18.6%), AVR and CABG (10.0%), mitral valve plasty or replacement (14.0%), and AVR and aortic root reconstruction (ARR) (5.5%) in Kuopio University Hospital from January 2013 to December 2016. Univariate and multivariate Cox proportional hazards models were used for statistical analyses. Kaplan–Meier survival curves were generated. Results. Total 30-d mortality was 1.8%. By Cox regression analysis, predictors of 30-d mortality (hazard ratio [HR] [95% confidence interval [CI]]) included female gender (1.95 [1.00–3.77]), preoperative atrial fibrillation, (2.38 [1.12–5.03]) reduced haemoglobin level (3.40 [1.47–7.90]), and pulmonary congestion (3.16 [1.52–6.55]). The combination of preoperative reduced haemoglobin and preoperative atrial fibrillation was a strong predictor (12.37 [4.40–34.77], p  < .001). Estimated glomerular filtration rate (eGFR) predicted 30-d mortality in univariate models but was not an independent predictor in multivariate models. Conclusions. According to the main findings of our study, the combination of preoperative atrial fibrillation and reduced haemoglobin level substantially increase the risk of 30-d mortality after cardiac surgery. Identification of high-risk patients pre-operatively could help to make optimal clinical decisions for timing of operation and perioperative treatment.